Assessment of Soil Trace Metal Pollution in the Xuejiping Mine Area, Yunan, China. Issue 4 (28th February 2021) - Chen, Wen‐De; Yao, Wen‐Wen; Huang, Zhong‐Xuan; Ying, Qiao‐Chu; He, Zheng‐Wei
Abstract: Environmental pollution and risk assessment of trace metals in top soils of Xuejiping Mine in Xichang City are studied. Soil samples are collected around the mine areas. Seven trace metal elements (Hg, Cd, Pb, Cr, Cu, Zn, and As) are analyzed to evaluate the pollution status using chemical speciation, geo‐accumulation index ( I geo ), and the potential ecological risk index (RI). Results indicate that concentrations of trace metal elements in the mining area exceed soil background values in Yunnan Province. Trace metal elements are ranked according to the I geo evaluation results (indicating the degree of pollution), as: Pb > As > Cu > Hg > Zn > Cd > Cr; trace elements are ranked as E r i ( Hg ) > E r i ( As ) > E r i ( Cd ) > E r i ( Pb ) > E r i ( Cu ) > E r i ( Cr ) > E r i ( Zn ) using the ecological risk index. These results indicate that the surface soil of the Xuejiping mining area is moderately polluted by trace metal elements. Therefore, effective measures can be taken to control the trace metals pollution in the mining area (especially for Pb and Cu). Abstract : As people pay more attention to ecological problems, heavy metal pollution in mining soil has become a research hotspot in recent years. The ecological risk of seven trace metal elements in soil around Xuejiping mining area is evaluated by ecological evaluation method. Results provide a scientific theoretical basis for pollution prevention and control during stages of mining activities.